Features of idiopathic pulmonary alveolar proteinosis in high resolution computed tomography - Mehrian, Payam (International Scientific Literature, Inc., 2014)
BACKGROUND: Although the crazy-paving pattern on computed tomography is characteristic for pulmonary alveolar proteinosis (PAP), it is not specific and has not been compared between idiopathic and secondary PAPs in the large studies. The aim of this study was to determine the high resolution computed tomography (HRCT) features of idiopathic PAP. MATERIAL/METHODS: HRCT images of 35 patients (mean age: 38±14years; 54.3% male) with idiopathic PAP (proved by bronchoalveolar lavage or biopsy) were reviewed by two experienced pulmonary radiologist and detailed findings were reported. RESULTS: The predominant HRCT presentation of PAP was interlobular septal thickening (ILST;100%) and ground glass opacities (GGOs; 91.7%), resulting in crazy-paving pattern (83%). All patients had diffuse bilateral lung involvement that was symmetric in 97%. ILST and GGO without crazy-paving were seen in 17% and 14.7%, respectively. The overall extent of parenchymal involvement was 50 to 75% in 80% of patients. Thirty three cases (94%) had areas of geographic sparing within the affected lung. Peripheral sparing was seen in 85.7% of patients, including three patterns with some overlap: costophrenic angle (80%), apices (60%), and subpleural (57%) sparing. Other HRCT findings were: consolidation (63%), pulmonary nodules (31.4%), mediastinal and/or hilar lymphadenopathy (23%), mass-like consolidation (17%), pleural effusion (8.6%), and honey combing (5.7%). All female patients (n=16) had crazy-paving, while 13 out of 19 (68%) male patients had crazy-paving on their lung HRCT (p=0.02). CONCLUSIONS: This study demonstrated that the predominant HRCT presentation of idiopathic PAP was interlobular septal thickening and ground glass opacities, resulting in crazy-paving pattern.